Implementation and Outcomes of a Community-Based Pulmonary Rehabilitation Program in Rural Appalachia. Issue 4 (July 2017) - Doyle, Daniel; Tommarello, Chaffee; Broce, Mike; Emmett, Mary; Pollard, Cecil
Abstract : Purpose: To report on the implementation and clinical outcomes of a community-based pulmonary rehabilitation program in rural Appalachia. Methods: Three rural health centers and a large referral hospital worked together to establish pulmonary rehabilitation services based on AACVPR guidelines. Each site hired at least 1 respiratory therapist. To measure clinical outcomes, a retrospective medical record study compared pre- and post-program values for the modified Medical Research Council dyspnea level, 6-minute walk test (6MWT), negative inspiratory force (NIF), respiratory disease knowledge, St George Respiratory Questionnaire (SGRQ), BODE index (body mass index, airflow obstruction, dyspnea and exercise capacity), and smoking status. The percentages of persons completing the program and participating in maintenance exercise after the program were recorded. Results: During the first 20 months of the program, 195 unduplicated persons with qualifying chronic lung diseases started the program. Of these, 111 (57%) completed the program. Mean improvements for all 6 measures were highly significant ( P < .001) and compared favorably with published results from hospital-based programs: dyspnea level, −1.2; 6MWT, +259 ft; NIF, +11.3 cm H2 O; knowledge test, +1.9; SGRQ, −6.2; BODE index, −1.1. Of the 23 smokers, 5 quit by the end of the program. Conclusions: Community-based pulmonary rehabilitation in rural health centers is feasible and achieves clinical outcomes similar to programs in large hospitals and academic centers. Furthermore, the addition of respiratory therapists to these primary care teams provides important collateral benefits for the evidence-based care of patients with chronic lung diseases. Abstract : We report on a guideline-consistent pulmonary rehabilitation program at 3 rural health centers in West Virginia. In the first 20 months, 195 enrolled and 111 completed the program (57%). Improvements in outcome measures were highly significant and comparable to large centers, including 6-minute walk test, +259 ft; BODE index, −1.1; and St George Respiratory Questionnaire, −6.2.